Total Genomic DNA Extraction Studies from Seaweeds - Basyar, Wildan Mujahidul; Pharmawati, Made; Astarini, Ida Ayu (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 1 (2020): ATBES, 2020)
One of marine resources that has high value is seaweed.  Seaweed is a carrageenan producer used in the food industry. Seaweed contains many minerals, vitamins and proteins that are useful for health. Carotenoids are pigments found in seaweed that function as antioxidants.   The genes involved in carotenoid biosynthesis have been studied and provide opportunities for genetic improvement of seaweed.  DNA is a basic requirement in molecular analysis. Therefore, a suitable method of DNA extraction from seaweed is needed.  The aim of this research was to investigate DNA extraction method from several seaweed species and test the DNA quality through PCR-RAPD.  Seaweed samples were collected from Pantai Bumi Perkemahan Taman Nasional Bali Barat and DNA was extracted using Doyle and Doyle’s method with modifications.  PCR-RAPD was conducted using primer UBC127 and OPD 11 to test the quality of DNA.  Results showed that 3 hours incubation in 60ºC had the best result of DNA extraction.  However, the quality of DNA was low, as indicated by inconsistent PCR-RAPD products.   Further optimization in DNA extraction is needed to obtain high quality DNA for genetic analysis.